Unraveling the physiological and molecular mechanisms regulating grain yield under combined drought and heat stress in wheat (Triticum aestivum) - MEENA, SHASHI; TARIA, SUKUMAR; YADAV, SHEEL; KUMAR, SUDHIR; PUSHKAR, SUCHITRA; CHINNUSAMY, VISWANATHAN; KUMAR, RANJEET R; PADARIA, JASDEEP C (The Indian Journal of Agricultural Sciences, 2023)
An experiment was conducted during winter (rabi) seasons of 2020–21 and 2021–22 at the research farm of ICAR-Indian Agricultural Research Institute, New Delhi to assess the impacts of heat and drought stresses, both individually and combined, on wheat (Triticum aestivum L.) plants during the reproductive stage. Four wheat genotypes (C306, HD2967, Raj3765 and WL711) were subjected to heat stress (H), drought stress (D) and combined heat, and drought stress (HD) conditions at the anthesis stage. The research investigated various physiological, biochemical and grain yield parameters, as well as the relative expression of genes involved in the proline and abscisic acid (ABA) metabolic pathways. Among the tested genotypes, Raj3765 exhibited decreased ABA levels and increased proline accumulation during the anthesis stage under both individual and combined stress conditions. Notably, Raj3765 also displayed higher grain yield compared to the other 3 genotypes under all stress conditions, indicating that elevated proline levels and reduced ABA levels likely contributed to its resilience. Furthermore, the study revealed that the combination of heat and drought stresses had a more severe detrimental effect on wheat plants compared to individual stress treatments. These findings underscore the significance of comprehensively studying combined stress conditions, as they can result in substantial yield losses in wheat crop development and productivity.